KARAKTERISTIK GULA CAIR DARI AMPAS PADAT PRODUK BREM DI PERUSAHAAN Fa. UDIYANA PADA PERLAKUAN KONSENTRASI H2SO4 DAN WAKTU HIDROLISIS - Novita Dewi, Karina; Wrasiati, Luh Putu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Solid dregs of brem was a waste from the production of brem drinks that still had high nutrient content to be processed into liquid sugar. The method was used acid hydrolysis with H2SO4. This study aims to determine the effect of H2SO4 concentration and hydrolysis time on liquid sugar characteristics and determine the concentration of H2SO4 and the best hydrolysis time to produce liquid sugar. This study was used a Randomized Block Design of a factorial pattern consists of two factors. The first factor was H2SO4 96% concentration (0.2%, 0.4%, and 0.6%). The second factor was hydrolysis time consists (10, 20, and 30 minutes). The experiments were grouped into 2 groups to obtain 18 experimental units. The observed variables were reduction sugar, total sugar, yield, and color intensity (L *, a *, b *). The results showed that the interaction of H2SO4 concentration and hydrolysis time had no significant effect on reduction sugar, total sugar, yield, color intensity (L *, a *, b *). H2SO4 concentration has no effect on reduction sugar, total sugar, yield, color intensity (L *, a *, b *). The hydrolysis time affects the reduction sugar, total sugar, yield, and brightness (L *) but does not affect the redness (a *) and yellowness (b *). The best treatments were obtained based on reduction sugar content and material usage efficiency was 0.2% H2SO4 concentration and hydrolysis time of 20 minutes with characteristic of reduction sugar 7.20 mg / l, total sugar 17.47 mg / l, yield 36.00%, brightness (L *) 9.01, redness level (a *) -2.23, and yellowness (b *) 32.50. Keywords : solid dregs of brem, hydrolysis, H2SO4, liquid sugar